If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 9 = -8t + -13 Reorder the terms: 9 + 2t = -8t + -13 Reorder the terms: 9 + 2t = -13 + -8t Solving 9 + 2t = -13 + -8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8t' to each side of the equation. 9 + 2t + 8t = -13 + -8t + 8t Combine like terms: 2t + 8t = 10t 9 + 10t = -13 + -8t + 8t Combine like terms: -8t + 8t = 0 9 + 10t = -13 + 0 9 + 10t = -13 Add '-9' to each side of the equation. 9 + -9 + 10t = -13 + -9 Combine like terms: 9 + -9 = 0 0 + 10t = -13 + -9 10t = -13 + -9 Combine like terms: -13 + -9 = -22 10t = -22 Divide each side by '10'. t = -2.2 Simplifying t = -2.2
| 51n^2+17n=0 | | 20w-100=20w-100 | | 20-4w/3=-w | | 8(r-3)+1=17 | | -2(-16)+9= | | 2x+1.50*.015=11.50 | | 25y^2+15y=0 | | 13-(2X-5)=(X+2)+3X | | 9y-4-5y+1=0 | | -3n(n-3)+4(n+4)= | | 4m+9m=91 | | x-20+153=180 | | ax-b=4c | | -3n(n-3)= | | -5a-4a= | | x^3+7x^2+5x-28=0 | | 5v^2+29v+36=0 | | n3-8=-2 | | x^2-2x-48=X^2 | | a^2-12a-12=0 | | y^2-8y+41=0 | | 4(5-w)/3=-w | | 8z-6z=1 | | 2x^2-2x-48=X^2 | | -2(x-5)=6x+3 | | 2(3z-1)=3(z+2) | | y^2-6y+34=0 | | 8x+2=10x-8 | | 2y+1-17=.5 | | -7-9=2w+2w | | -8=3x-9 | | -4(x+3)=2x-3 |